Design and programming of a fault analysis tool to operate with a digital fault recorder (2017)
"This document presents the work developed as graduation project in electronic engineering by Alexei Rodriguez. It deals with the development of a transmission line fault analysis computer tool that includes fault location by impedance methods, fault detection by Clarke transform, fault trajectory and phasorial fault analysis. The final result is a tool programmed in LabVIEW that operates linked to a playback module that repeats a fault signal and a DFR module that generates a COMTRADE file which is the input of the tool and is the source of the fault analysis, which performs fault location with an error under 2% and fault detection under a quarter cycle". -- Tomado del Formato de Documento de Grado.